(untitled) (Journal of Enam Medical College, 2014)
Background: Hypokalemia is a very common electrolyte imbalance in diabetic patients which leads to substantial morbidity and mortality. Severe hypokalemia is associated with lifethreatening arrhythmias and sudden cardiac death. There are no adequate studies regarding the incidence and factors precipitating hypokalemia in Bangladeshi diabetic subjects. Objective: The objective of this study was to find out the factors precipitaing hypokalemia in diabetic patients. Materials and Methods: A total 95 admitted diabetic patients with hypokalemia were studied. Specimens were collected from all adult diabetic patients with serum potassium level <3.5 mmol/L irrespective of cause of admission. Informations were obtained in a semistructured data collection form and analyzed. Results: Most of the subjects (61.1%) belonged to the age group of 60 years and above, 31.5% to the age group 4059 years and 7.4% belonged to the age group of 2039 years. Sixty one (64.2%) patients were females and 34 (35.8%) were males. In 63.2% cases, vomiting was found as a factor causing hypokalemia in the diabetic patients. Other common factors precipitaing hypokalemia were diarrhea (42.1%), inadequate diet (9.5%), severe hyperglycemia (3,2%), diabetic ketoacidosis (6.3%) and drugs especially diuretics (18.9%), bronchodilators (6.3%) and steroids (5.3%). The commonest comorbidity associated with diabetes was hypertension. Conclusion: In this study the commonest precipitating factor causing hypokalemia was vomiting. Majority of hypokalemic patients were female and of older age group. When hypokalemia is identified, the underlying precipitating factor should be sought and the disorder treated. Diuretics should be used with caution in the elderly patients having hypertension, a common comorbid condition of diabetes, as these patients are susceptible to develop hypokalemia. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20940 J Enam Med Col 2014; 4(3): 145-150